If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 5) + -2(x + -4) = 12 Reorder the terms: x(5 + x) + -2(x + -4) = 12 (5 * x + x * x) + -2(x + -4) = 12 (5x + x2) + -2(x + -4) = 12 Reorder the terms: 5x + x2 + -2(-4 + x) = 12 5x + x2 + (-4 * -2 + x * -2) = 12 5x + x2 + (8 + -2x) = 12 Reorder the terms: 8 + 5x + -2x + x2 = 12 Combine like terms: 5x + -2x = 3x 8 + 3x + x2 = 12 Solving 8 + 3x + x2 = 12 Solving for variable 'x'. Reorder the terms: 8 + -12 + 3x + x2 = 12 + -12 Combine like terms: 8 + -12 = -4 -4 + 3x + x2 = 12 + -12 Combine like terms: 12 + -12 = 0 -4 + 3x + x2 = 0 Factor a trinomial. (-4 + -1x)(1 + -1x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-4, 1}
| r+16=2r+1 | | 4x+6=x-2y | | 4x+x=51 | | X-2(2x-7)=2(x-8) | | 186x=1132-16 | | abs(3x+4)=-3 | | w-(-8)=47 | | -4.8=3.2 | | 25+10(12-x)=5(3x-7) | | 41x-12(x-4)= | | 20=20*log(x) | | 7x+17x-7=6(4x+10) | | x^2+5x-2x=12-8 | | 0.25x+25=0.50x+15 | | -3.268=0.3k-0.7 | | 0.5x+3=0.75-7.75 | | -5(6k+9)=-27+7k | | 20=20log(x) | | 0.4-0.107= | | 78=1/2h(5+8) | | 5.6x+3=4.6x | | 2x-(6x-4)=8-4x | | 10-7x=-(x-12) | | 16x=-50 | | 3y-20=40 | | 8k-2=4 | | Y^2+3y=x^3-x | | 3w-4=4w | | 18(x+3)=2(9x+2)+50 | | 5b-3=-9 | | 4n+15=4n+15 | | 8x+7(-3x-6)=-52-3x |